Multi-Grade Teaching: Experiences of Elementary Teachers of Zone 2, DepEd Division of Zambales, Philippines - Wilbert B. Fronda; Marie Fe D. De Guzman; Leila L. Ravana (Future Science / FSH-PH Publications, 2026)
This study aimed to deeply understand the lived experiences of elementary teachers in multi-grade classrooms in Zone 2, Division of Zambales, Philippines. Employing a qualitative, phenomenological research design, the methodology involved in-depth interviews and observations with 15 purposively sampled multigrade teachers from Botolan and Palauig Districts. Data analysis was systematically conducted using Braun & Clarke's six-step thematic process. Key findings revealed that multigrade teaching is both highly demanding and deeply fulfilling. Teachers face significant challenges, including adapting to diverse learners and curricula, managing limited resources, and handling intensive planning and workload, often leading to emotional strain. Despite this, they derive sense of satisfaction from witnessing student growth, fostering strong learning communities, and experiencing personal and professional transformation. Teachers employ multifaceted coping strategies such as determination, proactive approaches, for instance differentiated instruction; and building supportive classroom communities. The study concludes that these educators exhibit remarkable resilience and ingenuity, and their effectiveness hinges on a robust, interconnected support system encompassing specialized professional development, adequate resources, and comprehensive collaborative and administrative backing.